Respuesta :
Answer:
Josh is wrong.
Step-by-step explanation:
5^-x / 5^x = 5^(-x-x) = 5^-2x
= 1 / 5^2x
(you subtract the exponents when dividing )
So Josh is wrong ( he would be correct if we were multiplying)
Answer:
Josh claim is not correct.
Step-by-step explanation:
Given : Josh examines the expression [tex]5^{-x}[/tex] over [tex]5^x[/tex], where m is greater than 0.
He claims that the expression has a value equal to 1 because it simplifies to [tex]5^0[/tex], and any integer to the 0 power is 1.
To find : Is Josh correct? Explain why or why not.
Solution :
We first solve the Josh expression,
[tex]5^{-x}[/tex] over [tex]5^x[/tex]
i.e. [tex]\frac{5^{-x}}{5^x}[/tex]
We know, [tex]\frac{x^a}{x^b}=x^{a-b}[/tex]
So, [tex]\frac{5^{-x}}{5^x}=5^{-x-x}[/tex]
[tex]\frac{5^{-x}}{5^x}=5^{-2x}[/tex]
His claim is not correct.
As the correct solution is [tex]\frac{5^{-x}}{5^x}=5^{-2x}[/tex]